HUBUNGAN KECERDASAN EMOSIONAL DENGAN KUALITAS INTERAKSI SOSIAL SISWA DI SMK PANCA ABDI BANGSAKU (PABAKU), STABAT-LANGKAT - Sri Ramadhani; Indo Mora Siregar; Dwi Nursiti; Lestari Dakhi (JURNAL PSYCHOMUTIARA, 2020)
This research is motivated by some examples of cases that occurred in SMK Panca Abdi Bangsaku (PABAKU) which there are students / I in SMK PABAKU who do cases from 2012-2016 school year case examples are Fight Teachers, fights between students, smoking in school environment, watching porn and absent movies are on the rise. This suggests that students / I have not been able to improve their emotional intelligence that can impede the process of social interaction with their friends. This study aims to determine the relationship of emotional intelligence with the quality of social interaction of students, know the emotional intelligence of students, and to know the quality of social interaction of students in SMK PABAKU. This research uses quantitative research approach. The population in this research is 265 with sampling technique is Random Sampling 72. The result of rxy correlation test is 0.612, where the hypothesis test r shows that the price of r count 0.612> r table (df = n-2; 72-2) 0.195. It means Ha is accepted and Ho is rejected or there is a relationship of Emotional Intelligence with Social Interaction of students in SMK Panca Abdi Bangsaku Stabat-Langkat. The conclusion of the result of this research is there is correlation of emotional intelligence with quality of social interaction of student. It is suggested to students / I to be more active in activities that are inside school and outside school, for further researcher can add insight, and for institution able to develop and support activity at student / I SMK PABAKU.